2020
DOI: 10.1016/j.ssmph.2019.100529
|View full text |Cite
|
Sign up to set email alerts
|

Associations between obesity and neighborhood socioeconomic status: Variations by gender and family income status

Abstract: ObjectivesTo analyze if the association between obesity and neighborhood socioeconomic status (SES) was moderated by gender and family income.MethodsData from 19,448 individuals 18 and older from the 2001–2008 National Health and Nutrition Examination Survey (NHANES) were geo-matched with social and built environment characteristics from the 2000 Census and other data sources. Objective height and weight measures were used to create body mass index (BMI) and obese status (BMI≥30). Tracts were divided into four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 32 publications
2
19
1
Order By: Relevance
“…It is also possible that socioeconomic inequalities in comorbidity might manifest differently at older ages in the two cohorts which can be examined in the future. Socioeconomically disadvantaged women are more vulnerable to obesity and depression compared to men, yet our study found no sex differences in socioeconomic inequalities in comorbidity(33-36).…”
Section: Discussioncontrasting
confidence: 74%
“…It is also possible that socioeconomic inequalities in comorbidity might manifest differently at older ages in the two cohorts which can be examined in the future. Socioeconomically disadvantaged women are more vulnerable to obesity and depression compared to men, yet our study found no sex differences in socioeconomic inequalities in comorbidity(33-36).…”
Section: Discussioncontrasting
confidence: 74%
“…9 For example, a recent analysis of the National Health and Nutrition Examination Survey found that neighborhood SES was positively associated with healthy body weight in women but not in men. 15 Other factors such as psychosocial stress may also play a significant role. 16 To the authors' knowledge, this is the first study to examine the joint influence of obesity and neighborhood characteristics on urinary stone risk parameters among stone formers.…”
Section: Discussionmentioning
confidence: 99%
“…These gender inequities in obesity and diabetes status also vary by income. Gender inequities in obesity prevalence are greater in lower-income communities than higherincome communities, with females having a higher prevalence of obesity than males [19,20]. Higher levels of the liver enzymes, ALT, AST, and GGT, have been found among Blacks compared to Whites, indicating that Black adults are at a higher risk of having diabetes than White adults [21], which supports substantial previous evidence of Black-White inequities in obesity [22][23][24][25] and diabetes [26].…”
Section: Introductionmentioning
confidence: 99%